Facing the challenge of learning and teaching gold mining grade 11 in the new curriculum : a self-study. - Ndhlovu, Majabulile (My University, 2012)
The South African government that was elected in 1994 made tremendous changes in the Education system. The new government came up with the new curriculum for Basic Education (grade R- 12). The new curriculum had new topics in physical science. This made me as a teacher doubt whether I would be able to teach new topics. During my time as a student, I was not taught mining at school or college. As a result, I decided to do a self study in order to investigate how I would learn gold mining as a topic in order for me to be able to teach it to my learners. My study involved studying my own teaching practice while learning and also finding out the key things that made me understand the content knowledge involved in the topic of gold mining. The self study was done in order to ensure that I understood the content knowledge and how best to teach it to the learners. I used a collaboration team, reflective journal, group interviews classroom observation and learners’ responses to collect data. The participants were my grade 11 learners and myself. My data was analysed using a PCK model, CoRes and PaPeRs. I had to learn the content knowledge and transform it to make it understandable to learners. I designed lessons using the prior knowledge of learners and integrating Physical Science and Geography. Lessons did not go as smoothly as I had expected. Learners wanted some of their existing knowledge to be included. The classroom activities depended entirely on the relationship between the teacher and learners. I carried out my study bearing in mind that implementation of the new curriculum depends not only on classroom interactions (DoE, 2002) but most importantly on the content knowledge that the teacher has and how it is transformed. Learners taught me to understand gold mining from the geographical point of view as well from the scientific point of view. From the beginning of the study they were really excited and were looking forward to new things. Using the learners’ science prior knowledge helped me design lessons that allowed me to learn to be a facilitator.
Keywords: Content knowledge; Gold mining; National Curriculum Statement; Curriculum 2005; Chemical systems; Pedagogical Content Knowledge (PCK); Content Representation (CoRe); Pedagogical and Professional experience Repertoires (PaP-eRs)